2020
DOI: 10.3389/fimmu.2020.01443
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in the Diagnosis and Prognosis of Sarcoidosis: Current Use and Future Prospects

Abstract: Sarcoidosis is a heterogeneous disease in terms of presentation, duration, and severity. Due to this heterogeneity, it is difficult to align treatment decisions. Biomarkers have proved to be useful for the diagnosis and prognosis of many diseases, and over the years, many biomarkers have been proposed to facilitate diagnosis, prognosis, and treatment decisions. Unfortunately, the ideal biomarker for sarcoidosis has not yet been discovered. The most commonly used biomarkers are serum and bronchoalveolar lavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 171 publications
(295 reference statements)
1
70
0
2
Order By: Relevance
“…In sarcoidosis, a variety of potential biomarkers have been investigated in serum, bronchoalveolar lavage, and imaging. 29 An ideal biomarker for sarcoidosis has not been discovered yet. Hypercalcemia, hypercalciuria, changes in vitamin D metabolism, increased ACE, or soluble interleukin-2 receptor (sIL-2R) levels, although inconclusive, may be associated with renal sarcoidosis and support its diagnosis ( Table 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…In sarcoidosis, a variety of potential biomarkers have been investigated in serum, bronchoalveolar lavage, and imaging. 29 An ideal biomarker for sarcoidosis has not been discovered yet. Hypercalcemia, hypercalciuria, changes in vitamin D metabolism, increased ACE, or soluble interleukin-2 receptor (sIL-2R) levels, although inconclusive, may be associated with renal sarcoidosis and support its diagnosis ( Table 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several biomarkers have been proposed for diagnosis and prognosis of sarcoidosis [ 27 , 28 ]. They include serum measurement of angiotensin-converting enzyme (SACE), sIL2-R, serum amyloid A and chitotriosidase, as well as calcium metabolism, particularly calcium in urine, broncho-alveolar cell counts, and 18F FDG PET/CT.…”
Section: Diagnosis Of Extrapulmonary Organ Sarcoidosismentioning
confidence: 99%
“…Grunewald J et al, reported the role of CD4 cells in granuloma development, involving epithelioid cells, giant cells 17 , macrophages/mononuclear phagocytes, and CD41 T cells with a few CD81 T cells around the periphery. These cells are closely correlated with CD41 T lymphocytes, whereas immunoglobulin (Ig) A-producing plasma cells, CD41, Th17 cells, T reg (T-regulatory cells), and B lymphocytes are involved in many inflammatory and autoimmune diseases.…”
Section: Fig 1: Pathogenesis Of Development Of Granuloma In Sarcoidosismentioning
confidence: 99%
“…Moreover, the amount of AV2S3+ BALF T in the granuloma cells of sarcoidosis has been positively related to prognosis. The presence of AV2S3+ T cells has been found to offer a protective action against the granuloma of disease 4,17 .…”
Section: T Cell Receptor (Tcr) Genesmentioning
confidence: 99%